Analysis of macular structure in age-related cataract patients with different antibody levels of severe acute respiratory syndrome coronavirus-2 vaccine - Li, Xiaochun; Cao, Xiaoguang; Pan, Zhongting; Sun, Xinping; Bao, Yongzhen (Frontiers in Immunology, 2022)
Objective To analyze the macular structure of age-related cataract (ARC) patients with different antibody levels after COVID-19 vaccine injection, in order to obtain the effect of COVID-19 vaccine on the macular structure, and speculate whether the COVID-19 vaccine has adverse effects on the macular structure. Methods This retrospective study is conducted to analysis on the status of COVID-19 vaccine and the thickness of different layers at different positions in the macular area of ARC patients. In the age, sex and eye axial length matched population, in the un-injection, no-antibody, IgM and IgG positive groups after vaccination, the choroid, ganglion cell complex, nerve fiber layer and retinal thickness at different positions of ETDRS zoning in the macular area were discussed. Results A total of 164 patients (164 eyes) were included in the analysis. There were 63 males and 101 females. The average age was 65.99 ± 8.43 years. There was no significant difference in age and sex among the groups (p>0.05). The average axial length of 164 eyes was 23.56 ± 1.46mm, and no significant difference between the groups (p>0.05). Non parametric test and ANOVA test for the thickness of choroid, retina, ganglion cell complex and retinal nerve fiber layer in each division of ETDRS showed no significant difference in the four groups of un-injection, no-antibody, IgM and IgG (p>0.05). There was no correlation between the antibody concentration and the thickness of macular structure (p>0.05). Conclusion There was no significant difference in the thickness of choroid, retina, ganglion cell complex and retinal fiber layer in different macular areas after COVID-19 vaccine injection. There was no linear correlation between the thickness of choroid, retina, ganglion cell complex and retinal fiber layer and the antibody concentration produced after COVID-19 vaccine injection. It suggests that the injection of COVID-19 vaccine might have no significant effect on the macular structure of eye.